An Evaluation of the Diversity of the Film Market for Cinema and Video Recordings in France and in Europe - Florence Lévy-Hartmann
The issue of cultural diversity is examined from the point of view of the diversity of the market for films shown in cinemas and films released as video recordings in the 2000s, based on a new sample of 5,600 films shown in cinemas, and 6,500 video film recordings. For both markets, the method used consisted of measuring diversity based on the criteria of variety, balance and range. The issues of increased supply (films), distribution (copies) and demand (number of tickets or video recordings sold) are covered for 6 European countries, namely: France, Denmark, Spain, Poland, the UK and Sweden. The video film market is covered for France only. The method used tends to indicate that France has the most diverse cinema film market, whilst its video film market is considerably less diverse. It confirms differences in diversity according to marketing channels whilst new research shows a higher level of diversity within the internet video film market.